The Hamzat al-Wasl and al-Qat’a in Al-Luma’ and its Annotations: A linguistic Study - Quam, Yathrib Usama (Al-Adab Journal, 2022)
The hamzat of Qata’ and wasl is one of the phonetic phenomenon in the Arabic language, and Ibn Jinni paid great attention to it in his book Al-Luma’ in Arabic, as he proceeded to differentiate between them according to linguistic features(phonetic, morphological, grammatical and semantic). The book Al-Luma’ has drawn the attention of a number of commentators, and they followed Ibn Jinni in codifying these rules to differentiate between the Hamzah Al-Qata’ and Al-Wasl and added to it. In the chapter on Hamzat al-Qata’ wa ​​al-Wasl, most of the rules were based on the pronunciation of the hamza and the non-pronunciation of it, and the distinction between the original and what is added to it. And that the name has two letters in the hamzat al-qata’ and is only on three or more letters in the hamzat al-wasl, and the differentiation relied on changing the hamza from al-wasl into al-qat’, from the singular case to the plural case. In addition, the research discussed the origins of the non-referenced names to show the origin of the connection in them, and the research shed light on some of the opinions that disagreed with Ibn Jinni and discussed them. It came on the authority of the commentators, and others that differed from Ibn Jinni, which are few, and a third that added to what he came with, in addition to the explanation and detail provided by the commentators of the opinions contained in the Book of Al-Lama’ regarding the hamzats of Qat’a and wasl.